Histopathological analysis of gangliosides use in peripheral nerve regeneration after axonotmesis in rats - Ribeiro,Camila Maria Beder (2008)
PURPOSE: To analyze the action of gangliosides in peripheral nerve regeneration in the sciatic nerve of the rat. METHODS: The sample was composed of 96 male Wistar rats. The animals were anaesthetized and, after identification of the anaesthesic plane, an incision was made in the posterior region of the thigh, followed by skin and muscle divulsion. The right sciatic nerve was isolated and compressed for 2 minutes. Continuous suture of the skin was performed. The animals were randomly divided into two groups: the experimental group (EG), which received subcutaneous injection of gangliosides, and the control group (CG), which received saline solution (0.9%) to mimic the effects of drug administration. RESULTS: No differences were observed between the experimental and control groups evaluated on the eighth day of observation. At 15 and 30 days the EG showed an decrease in Schwann cell activity and an apparent improvement in fibre organization; at 60 days, there was a slight presence of Schwann cells in the endoneural space and the fibres were organized, indicating nerve regeneration. At 15 and 30 days, the level of cell reaction in the CG had diminished, but there were many cells with cytoplasm in activity and in mitosis; at 60 days, hyperplastic Schwann cells and mitotic activity were again observed, as well as nerve regeneration, but to a lesser extent than in the EG. CONCLUSION: The administration of exogenous gangliosides seems to improve nerve regeneration.